Local variations of ecosystem functions in Mediterranean evergreen oak woodland (Ann. For. Sci., 1996)
The spatial variation of ecosystem function was studied in a Quercus ilex coppice growing on hard limestone with low soil water availability. Spatial structures obtained from data on i) leaf area index, ii) leaf litterfall, and iii) leaf litter decay rate were compared. All these variables were sampled on 26 points located within a 30 x 30 m plot. Mean average leaf litterfall over 10 years (1984-1993) was 254 g.m-2. For each year, the semivariograms of leaf litterfall have been fitted using a spherical model. The values of the range parameter (indicating the limit of the spatial dependence) ranged from 6.4 to 10.3 m, very close to the value (9.2 m) of the range parameter obtained when fitting the semivariogram of mean leaf litterfall over 10 years. This result indicates the temporal persistence of the spatial pattern of leaf litterfall. The leaf area index (LAI) was estimated at the same points with a plant canopy analyzer. The mean value was 2.96 ± 0.30. The limit of spatial dependence for LAI was very close to that obtained for leaf litterfall (range = 8.5 m). The litter decomposition pattern was obtained through analysis of litter samples taken at the same points. The percentage of ash-free litter mass remaining (LMR) estimated using near-infrared reflectance spectroscopy indicates the stage of decomposition. It decreased strongly between the surface (mean value 85.6%) and the subsurface layers (mean value 63.4%). The two semivariograms can be described by spherical models, the sill being reached at a range of 21.4 and 18.7 m for the surface and subsurface layers, respectively. The two variables directly related to the structure of the canopy (LAI and leaf litterfall) exhibited close spatial dependence and differed from the soil process-related variables (stage of decomposition) whose ranges were approximately double. These geostatistical analyses show promise for use in developing hypotheses concerning the spatial scale of process-pattern interactions.

NATURAL GERMINATION AS RESILIENCE COMPONENT IN MEDITERRANEAN COPPICE STANDS OF CASTANEA-SATIVA MILL AND QUERCUS-ILEX L (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 1994)
In the Mediterranean basin, most of the present forests derive from original forests where the dominant species was different from the present one. These changes are largely due to human activities reflecting millenia of management and, often, overexploitation. In southern France, for example, palaeoecologists believe that the original malacophyllous deciduous forest of downy oak (Quercus pubescens) was replaced by a sclerophyllous evergreen holm oak (Quercus ilex) coppice in the driest areas, and chestnut (Castanea sativa) orchards or coppices in the `'wettest'' areas. However, for the last several decades, exploitation of these coppice stands has been decreasing. In this study, we addressed the question of the resilience of these managed ecosystems in the fact of changing management schemes, and to determine appropriate strategies and criteria of sustainable development. We present some aspects of the auto-succession after clearcutting of holm oak coppice stands and aspects of the natural regeneration of 4 species (Q. ilex, Q. pubescens, C. sativa, and P. pinaster). The consequences of the contrasted life history strategies are compared to estimate the future of these coppices.

Germination and regeneration mechanisms in Mediterranean degenerate forests (Journal of Vegetation Science, 1993)
Abstract. Germination and developmental behaviour during juvenile stages are of importance in relation to succession mechanisms acting on plant communities. This is particularly so in the Mediterranean region, where the climatic summer drought causes stress. We investigated and compared germination and development of four tree species in two parts of the French Mediterranean region where the original dominant tree species (Quercus pubescens) has been largely replaced by Quercus ilex in the southern part, and Castanea sativa in the northern part. Observed differences in germination rates and developmental behaviour, especially shootroot ratio and the role of water supply, suggest that other species may eventually replace the current dominant species.

NATURAL DEGENERATE MEDITERRANEAN FORESTS - WHICH FUTURE - THE EXAMPLES OF THE HOLM OAK (QUERCUS-ILEX L) AND CHESTNUT (CASTANEA-SATIVA MILL) COPPICE STANDS (RESPONSES OF FOREST ECOSYSTEMS TO ENVIRONMENTAL CHANGES, 1992)
Primarily derived from the Quercus pubescens forest destroyed by overexploitation, the Quercus ilex and Castanea sativa coppice stands are two of the most widespread biocoenoses in the European Mediterranean area. Two of the questions we sought to answer were (i) in the case where the same disturbance persists, whether these coppice stands reach a state of “equilibrium” based on auto-succession or they continue to change, and (ii) in the case where disturbance stops, whether the present dominant species (Q. ilex or C. sativa) continues to be dominant (high resilience) or an other species (Q. pubescens ?) could replace it. A third case exists, i.e. a change of the “disturbance” in order to obtain a “sustainable” development, but, in that case, biological or socio-economical criteria must be defined. In order to highlight the first stages of these possible changes, germination abilities of these species were studied and compared. For Q. ilex coppice stands, it can be said that there would appear to be a partial allelopathic inhibition of Q. ilex germination, to which Q. pubescens is less sensitive. For C. sativa, this phenomenon was not found. We also briefly discuss the main characteristics of a programme which tests some biological criteria for a sustainable development.

Variations de la croissance radiale de Quercus ilex L en fonction du climat (Ann. For. Sci., 1991)
Diameter growth of Quercus ilex L and the interannual variability of climatic characteristics. Diameter growth of Quercus ilex L, the dominant sclerophyllous species in much of the Mediterranean basin vegetation, was studied in relation to precipitation and temperature. The study site in Montpellier (Southern France) has a Mediterranean climate. Eleven trees, grown from acorns in 1963, were cut in 1984 and the rings studied at 3 levels (ground, 0.5 and 1 m above the ground). The data were analyzed by the ARMA procedure which gives the part of the total variation due to the autocorrelation processes. A multiple regression between the factors of a principal component analysis (PCA) of the monthly climatic data (rainfall and temperature) and the residuals issuing from the ARMA procedure then suggested that the large annual rings were due to a particular rainfall distribution during the year, the late summer precipitation promoting a large annual growth diameter (table II). The presence or absence of false rings (table I) was also analyzed by PCA (figs 2 and 3). The false rings were positively correlated to a large annual growth diameter corresponding to a high summer rainfall (fig 4), while the relationship with the temperature preceding the growing season was negative. It therefore appears that this species is relatively unaffected by spring climatic conditions, ie which generally indicate the main growth phase, but that it is able to take advantage of the interannual climatic variations of the region.

Germination of Quercus ilex and Q. pubescens in a Q. ilex coppice (Plant Ecology, 1990)
Quercus ilex L. (holm oak) coppices, widespread around the Mediterranean basin, are probably the result of 5 000 years of prolonged human disturbance of the original Quercus pubescens Willd. (downy oak) forests. Since disturbance has almost ceased in recent years, a question arises as to the development of these coppices: will the Q. pubescens forests return, or will Q. ilex remain the dominant species? To investigate the phenomenon, we analyzed the first stages, i.e. germination of the two species in holm oak coppices. Our experiments show that both species germinated better in coppices than in clearings or clear-cuts. Moreover, Q. pubescens appears to be slightly favored above Q. ilex and it is suggested auto-allelopathy is involved, at least partially inhibiting the germination of Q. ilex.

Local characterization of vegetation through growth forms: Mediterranean Quercus ilex coppice as an example (Plant Ecology, 1987)
Growth forms are considered from two viewpoints: a descriptive and a functional one. Mono-character growth forms and their biological spectra were used to test whether they can characterize certain underlying processes in Quercus ilex coppice in southern France. Correspondence analysis of 35 mono-character growth forms of 203 described taxa shows that location of renewal buds is a good integrating indicator of plant adaptations to the environment. Two of these characters (renewal bud location, Le. Raunkiaer's main life forms, and leaf consistency) appear to vary significantly along a gradient of increasing environmental constraints, especially climatic ones.

Methods of studing canopy cover of Quercus-ilex coppices (ACTA OECOLOGICA-OECOLOGIA APPLICATA, 1982)
APS